1998
DOI: 10.1161/01.cir.98.25.2905
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Interaction Between ATP-Sensitive K + Channel and Na + ,K + -ATPase Modulates Ischemic Preconditioning

Abstract: Background-We reported that digoxin abolishes the infarct size (IS)-limiting effect of ischemic preconditioning (IPC).Because ATP-sensitive K ϩ (K ATP ) channels are involved in IPC, we studied whether Na ϩ ,K ϩ -ATPase and K ATP channels functionally interact, thereby modulating IPC. Methods and Results-Rabbits received 30 minutes of coronary artery occlusion followed by 3 hours of reperfusion. IPC was elicited by 5 minutes of occlusion followed by 10 minutes of reperfusion. The IS, expressed as a percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Numerous studies have demonstrated a role for Na/KATPase in the heart's response to ischemia reperfusion (39). Notably, a functional link between Na/K-ATPase and K ATP has also been described (27). Haruna et al (27) demonstrated that a coordinate interaction between the K ATP channel and Na/KATPase modulates ischemic preconditioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated a role for Na/KATPase in the heart's response to ischemia reperfusion (39). Notably, a functional link between Na/K-ATPase and K ATP has also been described (27). Haruna et al (27) demonstrated that a coordinate interaction between the K ATP channel and Na/KATPase modulates ischemic preconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins-In heart and other tissues, K ATP channel function has been tightly linked with the activity of the Na/K-ATPase (27,28). Notably, work from our group and others has demonstrated direct high affinity interaction of ankyrin with Na/KATPase (ankyrin-B in heart) and loss of membrane Na/K-ATPase in ankyrin-deficient cells (9, 29 -31).…”
Section: Ankyrin-b Organizes Complexes Of Functionally Related Membranementioning
confidence: 99%
“…The mechanisms involved in preconditioning are not fully understood, but may depend on the release of endog-Preconditioning with gentamicin of LLC-PK1 cells www.bjournal.com.br enous protective mediators such as adenosine (13), prostacyclin (14), bradykinin (15), nitric oxide (NO) (9), opening of K ATP channels (16), endothelin 1 decrease (17), and heat shock protein (HSP) synthesis (18). The protective effect of the initial preconditioning stress may involve the ability of tissue to induce HSP synthesis (19,20) and to increase NO production (21).…”
Section: Introductionmentioning
confidence: 99%
“…However, digoxin did not alter the protective effects of the K ATP opener, cromakalim, since K ATP channel openers would be expected to act directly on the channels, and thus, have effects independent of ATP concentrations. Furthermore, diazoxide, a selective mitoK ATP channel opener, failed to reduce infarct size when administered at a similar or 10-fold higher dose than that needed for cromakalim to produce its infarct-limiting effects [23]. This is of special note, given that Garlid et al [24] demonstrated that cromakalim and diazoxide display a similar degree of potency for opening mitoK ATP in reconstituted mitochondria and elicited a similar degree of cardioprotection following ischemia-reperfusion in the isolated rat heart.…”
Section: Sarck Atp As a Distal Effectormentioning
confidence: 91%
“…Haruna et al [23] recently reported that the infarct limiting effect of IPC may be modulated via an interaction between Na + -K + ATPase and sarcK ATP channels. In this study, the infarct-limiting effects of IPC in anesthetized rabbits were abolished by digoxin, an inhibitor of Na + -K + ATPase [23]. By inhibiting Na + -K + ATPase, digoxin would raise the amount of subsarcolemmal ATP, preventing the opening of the sarcK ATP channel during IPC.…”
Section: Sarck Atp As a Distal Effectormentioning
confidence: 99%